Educação corporativa e práticas gerenciais: um modelo relacional de estudo em uma empresa do segmento de varejo - Agnes Laila Calixto (2018)
This paper aims to verify the relationship between the corporate education and management practices from the point of view of managers, in the context of a large company in the retail segment, headquartered in São Paulo, and with subsidiaries located in the main Brazilian states. The research was carried out with 105 managers, who participated in corporate education programs in the selected company. Considering the objective, it was decided to carry out a quantitative research, in which the data collection was done through a questionnaire, using five-point Likert scales, with online application mode. The collected data were submitted to the statistical treatment that involved techniques of descriptive analysis, factorial analysis and modeling by structural equations. The theoretical reference of the work contemplated the approach of the principles and practices of corporate education proposed by Eboli (2004) and the managerial practices adapted from the model of Quinn et alii (2012). The results obtained allowed the identification of the practices of corporate education and the managerial practices prevalent in the company surveyed. Also, the validation of the measurement model for the theoretical model was verified. And, finally, the research results confirmed the existence of a positive and significant relationship between corporate education and management practices. In this sense, the importance of the advances for the research and for the development of this theme in other companies stands out